Vaccination to reduce antimicrobial resistance burden: data gaps and future research - Tadesse, Birkneh Tilahun; Keddy, Karen H; Rickett, Natasha Y; Zhusupbekova, Aidai; Poudyal, Nimesh; Lawley, Trevor; Osman, Majdi; Dougan, Gordon; Kim, Jerome H; Lee, Jung-Seok; Jeon, Hyon Jin; Marks, Florian (Clinical infectious diseases, 2023)
Antimicrobial resistance (AMR) poses an immediate danger to global health. If unaddressed, the current upsurge in AMR threatens to reverse the achievements in reducing the infectious disease-associated mortality and morbidity associated with antimicrobial treatment. Consequently, there is an urgent need for strategies to prevent or slow the progress of AMR. Vaccines potentially contribute both directly and indirectly to combating AMR. Modeling studies have indicated significant gains from vaccination in reducing AMR burdens for specific pathogens, reducing mortality/morbidity, and economic loss. However, quantifying the real impact of vaccines in these reductions is challenging because many of the study designs used to evaluate the contribution of vaccination programs are affected by significant background confounding, and potential selection and information bias. Here, we discuss challenges in assessing vaccine impact to reduce AMR burdens and suggest potential approaches for vaccine impact evaluation nested in vaccine trials.
Veröffentlicht: 20. Dezember 2023
Gesehen am 08.05.2024